Spatial metabolomics in mental disorders and traditional Chinese medicine: a review - Lei, Chaofang; Chen, Jiaxu; Chen, Zhigang; Ma, Chongyang; Chen, Xudong; Sun, Xiongxing; Tang, Xukun; Deng, Jun; Wang, Shiliang; Jiang, Junlin; Wu, Dahua; Xie, Le (Frontiers in Pharmacology, 2025)
Spatial metabolomics is an emerging technology that integrates mass spectrometry imaging (MSI) with metabolomics, offering a novel visual perspective for traditional metabolomics analysis. This technology enables in-depth analysis in three dimensions: qualitative, quantitative, and localization of metabolites. Spatial metabolomics precisely reflects the characteristics of metabolic network changes in metabolites within entire tissues or specific micro-regions. It provides a detailed understanding of the pharmacodynamic material basis and mechanisms of action. These capabilities suggest that spatial metabolomics can offer significant technical support for studying the complex pathophysiology of mental disorders. Although the mechanisms underlying mental disorders have been reviewed multiple times, this paper provides a comprehensive comparison between traditional metabolomics and spatial metabolomics. It also summarizes the latest progress and challenges of applying spatial metabolomics to the study of mental disorders and traditional Chinese medicine.